2019
DOI: 10.1177/0886260519863726
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Coping and Perceptions of Coping Efficacy After Sexual Abuse: Links to Trauma Symptoms

Abstract: Despite an emphasis on coping following childhood sexual abuse (CSA) to reduce trauma-related symptoms, very few studies have researched the associations between sexually abused children’s coping and trauma-related difficulties, and perceived coping efficacy has been largely overlooked. The current study investigated whether children’s use and perceived efficacy of avoidant, internalized, angry, and active/social coping strategies were associated with caregiver- and child-reported posttraumatic stress symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
(146 reference statements)
2
3
0
Order By: Relevance
“…In our study, about 87% of adolescents reported “distracting yourself from thinking about the problem” this result was similar to the study of Campbell et al ( 29 ), with 84.7% of adolescents reported “just tried to forget it” when they faced with a problem. There was 83.3% of adolescents reported “doing something else to stop thinking about the problem,” and 66.4% of adolescents reported “trying hard to fix the problem” those results were higher than the results of Campbell et al ( 29 ). The reason may be due to our research conducted in the context of the Covid-19 pandemic, and the culture in diffentce.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our study, about 87% of adolescents reported “distracting yourself from thinking about the problem” this result was similar to the study of Campbell et al ( 29 ), with 84.7% of adolescents reported “just tried to forget it” when they faced with a problem. There was 83.3% of adolescents reported “doing something else to stop thinking about the problem,” and 66.4% of adolescents reported “trying hard to fix the problem” those results were higher than the results of Campbell et al ( 29 ). The reason may be due to our research conducted in the context of the Covid-19 pandemic, and the culture in diffentce.…”
Section: Discussionsupporting
confidence: 91%
“…In line with the previous studies, children utilized a variety of strategies to cope with stress ( 28 31 ), reflecting a need for children to attempt to cope. Children most frequently reported using avoidant coping and social coping, findings that are consistent with the existing research ( 29 , 30 ). Children do not use a single strategy to cope, supporting speculation presented by other studíe that children essentially “try out” a large variety of strategies before determining which are effective and/or feasible ( 28 30 , 32 , 33 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Studies have shown that focused coping is commonly used by survivors of CSA. 24 The use of focused coping has been suggested to decrease negative symptoms and may be a better approach as compared to others. 36 Similarly, finding comfort in religion and spirituality as a coping strategy may have positive outcomes akin to the focused coping approach.…”
Section: Discussionmentioning
confidence: 99%
“…22 In a randomized controlled trial among 247 participants, Sikkema et al 23 reported that participants used avoidant coping (emotional suppression, denial and substance use) to deal with the stress associated with living with HIV and history of CSA. Similarly, to investigate children’s use of coping strategies, Campbell et al 24 reported that survivors of CSA used both adaptive and maladaptive coping strategies. Studies have shown that maladaptive coping strategies are strong predictors of adverse outcomes, including general distress, depression, reduced self-esteem and post-traumatic stress syndrome.…”
Section: Introductionmentioning
confidence: 99%